PILIHAN RASIONAL PENGELOLA GARUDA WISNU KENCANA MEMPERTAHANKAN KUNJUNGAN WISATAWAN DOMESTIK DI MASA PANDEMI COVID-19 (JURNAL ILMIAH SOSIOLOGI: SOROT, 2023)
The Covid-19 pandemic has affected all sectors of human life, especially the Bali tourism sector; for instance, it has caused the number of domestic tourists visiting Garuda Wisnu Kencana to decrease. This study used a qualitative approach to analyze the rational choice of Garuda Wisnu Kencana managers in maintaining domestic tourist visits during the Covid-19. Moreover, the result is further explained in the explanatory descriptive, and James S Coleman's Theory of Rational Choice is used as the theory for the analysis. There are two essential elements in rational choice: actors and resources. Zetlin suggests that there are five essential elements regarding the process of rational choices: determining the priority, measuring the resources and actions, selecting the actors, and exchanging the resources. Garuda Wisnu Kencana actors have maintained the resources intentionally with goals or interest from a value and choice and thorough consideration. The managers create new regulations based on the circumstances on the ground with a government's new binding regulation to decrease the virus's spreading.